Neurophysiological study of consumer emotional reactions in a simulated multisensory retail environment - Eremenko, Julia; Kosonogov, Vladimir; Aksiotis, Vladislav; Moiseeva, Victoria; Obukhova, Anastasia; Godovanets, Alisa; Zinchenko, Oksana; Klucharev, Vasily; Shestakova, Anna (Frontiers in Human Neuroscience, 2025)
IntroductionEmotions play a crucial role in shaping consumer experiences and decisions. Neurophysiological tools offer objective markers of emotional reactions in multisensory environments, where positive valence promotes approach behavior and negative valence fosters avoidance.MethodsWe applied the Osgood semantic differential (SD) to establish correspondences between visual, auditory, and olfactory stimuli and target emotions relevant to retail zoning. Based on SD results, we selected stimuli to create multisensory environments. These were presented in immersive virtual reality (VR) to 27 participants. Emotional responses were assessed via heart rate (HR), heart rate variability (HRV), and electrodermal activity (EDA).ResultsSD analysis identified cross-modal associations between sensory stimuli and retail zones, allowing refinement of semantic positioning. VR experiments revealed that HRV significantly increased in pleasant environments, indicating enhanced parasympathetic activation. HR and EDA showed no significant correlation with emotional valence, though both displayed trends toward reduction in pleasant conditions.DiscussionOur findings suggest that HRV is a reliable physiological marker of consumers’ approach behavior in multisensory retail environments, whereas HR and EDA are less sensitive. Combining SD with VR-based neurophysiological assessment enables objective evaluation of emotional zoning strategies, offering a scientifically grounded alternative to intuitive design practices for optimizing consumer experience.